The Agaricus bisporus cox1 Gene: The Longest Mitochondrial Gene and the Largest Reservoir of Mitochondrial Group I Introns - Férandon, Cyril (Public Library of Science, 2010)
In eukaryotes, introns are located in nuclear and organelle genes from several kingdoms. Large introns (up to 5 kbp) are frequent in mitochondrial genomes of plant and fungi but scarce in Metazoa, even if these organisms are grouped with fungi among the Opisthokonts. Mitochondrial introns are classified in two groups (I and II) according to their RNA secondary structure involved in the intron self-splicing mechanism. Most of these mitochondrial group I introns carry a “Homing Endonuclease Gene” (heg) encoding a DNA endonuclease acting in transfer and site-specific integration (“homing”) and allowing intron spreading and gain after lateral transfer even between species from different kingdoms. Opposed to this gain mechanism, is another which implies that introns, which would have been abundant in the ancestral genes, would mainly evolve by loss. The importance of both mechanisms (loss and gain) is matter of debate. Here we report the sequence of the cox1 gene of the button mushroom Agaricus bisporus, the most widely cultivated mushroom in the world. This gene is both the longest mitochondrial gene (29,902 nt) and the largest group I intron reservoir reported to date with 18 group I and 1 group II. An exhaustive analysis of the group I introns available in cox1 genes shows that they are mobile genetic elements whose numerous events of loss and gain by lateral transfer combine to explain their wide and patchy distribution extending over several kingdoms. An overview of intron distribution, together with the high frequency of eroded heg, suggests that they are evolving towards loss. In this landscape of eroded and lost intron sequences, the A. bisporus cox1 gene exhibits a peculiar dynamics of intron keeping and catching, leading to the largest collection of mitochondrial group I introns reported to date in a Eukaryote.